Determinan Jumlah Penduduk Miskin di Jawa Periode 2007-2015 - Mohammad Saleh; Mochammad Dwi Ainoer Rizzal; Aisah Jumiati (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
Poverty is one of the problems that impede economic growth and national and regional development. It is therefore necessary to find solutions to reduce poverty and solve the problems that are being experienced. The purpose of this study to determine the influence of unemployment, wages and Gross Domestic Product (GDP) on poverty in Java. This research method is explanatory research method. The unit of analysis used in this study is the number of poor people in Java, factors affecting poverty include unemployment, wages and Gross Domestic Product (GDP). Data used in this research is secondary data. The results showed that the positive effect of unemployment and wages and GRDP a significant negative effect on poverty. From the results of this study are expected later able to provide references improvements creation of the welfare of society equally. Keywords: People poverty, unemployment, wage, Gross Regional Domestic Produc